Ethnomelissological, melissopalynological and physicochemical characterization of honeys from the El Tarf region, Northeastern Algeria - Bergal, Amira; Boumaraf, Warda; Nefla, Loubna; Bouksiba, Chahrazed; Benouareth , Djamel (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2026)
Honey is a natural product produced by bees from floral nectar or plant secretions. This study evaluated apicultural practices and honey quality from the El Tarf region (northeastern Algeria) using an integrated approach combining ethnomellissological surveys, melissopalynological analysis, and physicochemical characterization. A total of 36 samples representing six honey types (white heather, eucalyptus, lavender, mountain, multifloral, and orange blossom) were collected from four localities (Aïn Khiyar, Zitouna, Bougous, and Aïn Karma). Pollen analysis revealed a predominance of polyfloral honeys with variable monofloral representation. Physicochemical parameters showed significant variability among honey types (p < 0.05), with pH ranging from 3.73 to 4.37, moisture content from 13.90 % to 18.19 %, and electrical conductivity from 330.33 to 719.33 µS.cm-1. Hydroxymethylfurfural (HMF) content varied between 41.35 and 49.80 mg.kg-1, while total acidity ranged from 41.50 to 63.64 meq.kg-1. Diastase activity (9.50–14.00 DN) and proline content (310–420 mg.kg-1) also showed significant differences according to botanical origin (p < 0.05). All samples complied with international honey quality standards. Principal Component Analysis (PCA) showed that honey samples were clearly structured according to botanical origin, with electrical conductivity, proline, and acidity contributing most to variability (PC1 = 46.38 %, PC2 = 28.04 %). Monofloral honeys exhibited more homogeneous profiles, whereas multifloral samples were more dispersed, confirming significant compositional variability (p < 0.05). The results demonstrate that honey quality in the El Tarf region is primarily influenced by floral origin and local beekeeping practices, highlighting the relevance of integrating traditional knowledge with physicochemical and palynological approaches for honey authentication and quality assessment.